Penggunaan Metode Iqra’ untuk Meningkatkan Kemampuan Mengenal Huruf Hijayyah pada Anak Usia 5-6 Tahun di Kota Mataram Tahun 2021 - Husna Mardiah Tillah; Nurhasanah Nurhasanah; Ika Rachmayani; Baik Nilawati Astini (Indonesian Journal of Elementary and Childhood Education, 2021)
This study aims to improve the ability to recognize hijayyah letters using the iqra' method in children aged 5-6 years in the Sayang Daye neighborhood, Sayang Sayang village, Mataram City. This type of research is descriptive qualitative research. The subjects in this study were children aged 5-6 years who revealed 3 children. Data were collected through observation and documentation methods. The data analysis used is descriptive qualitative analysis. The steps for using the iqra' method that can improve the ability to recognize the hijayyah letter in children aged 5-6 years are: (a) the introduction of the hijayyah letter, (b) the use of the iqra' method. The results obtained by the researchers obtained average results of 54%, 72% and 65% during April 2021. The indicator of the ability to recognize hijayyah letters in children aged 5-6 years in the Sayang Daye environment shows that two children are in the developing category as expected (BSH) and one child was in the category of starting to develop (MB). The conclusion is that the use of the iqra' method can improve the ability to recognize hijayyah letters in children aged 5-6 years in the Sayang Daye environment, Sayang Sayang Village, Cakranegara District, Mataram City which is carried out optimally.